Dissecting the Interaction Deficiency of a Cartilaginous Fish Digestive Lipase with Pancreatic Colipase: Biochemical and Structural Insights. (13th March 2020) - Achouri, Neila; Tomàs-Gamisans, Màrius; Triki, Soumaya; Valero, Francisco; Miled, Nabil; Fendri, Ahmed; Smichi, Nabil
Abstract : A full-length cDNA encoding digestive lipase (SmDL) was cloned from the pancreas of the smooth-hound ( Mustelus mustelus ). The obtained cDNA was 1350 bp long encoding 451 amino acids. The deduced amino acid sequence has high similarity with known pancreatic lipases. Catalytic triad and disulphide bond positions are also conserved. According to the established phylogeny, the SmDL was grouped with those of tuna and Sparidae lipases into one fish digestive lipase cluster. The recently purified enzyme shows no dependence for bile salts and colipase. For this, the residue-level interactions between lipase-colipase are yet to be clearly understood. The structural model of the SmDL was built, and several dissimilarities were noticed when analyzing the SmDL amino acids corresponding to those involved in HPL binding to colipase. Interestingly, the C-terminal domain of SmDL which holds the colipase shows a significant role for colipase interaction. This is apt to prevent the interaction between fish lipase and the pancreatic colipase which and can provide more explanation on the fact that the classical colipase is unable to activate the SmDL.